Structural analysis of how podocytes detach from the glomerular basement membrane under hypertrophic stress - Kriz, Wilhelm; Hähnel, Brunhilde; Hosser, Hiltraud; Rösener, Sigrid; Waldherr, Rüdiger (Frontiers in endocrinology, 2014)
Podocytes are lost by detachment from the GBM as viable cells; details are largely unknown. We studied this process in the rat after growth stimulation with FGF-2.
Gesehen am 14.10.2020